2019
DOI: 10.1155/2019/5320718
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Oestrus Cycles in Namibian Swakara and Damara Sheep through Determination of Circannual Plasma Progesterone Levels

Abstract: A year-long prospective study characterized the seasonality of oestrus cycles in primiparous, nonpregnant Swakara (n=8) and Damara (n=5) ewes through surveillance of plasma progesterone (P4) levels. During this period, Swakara and Damara groups evidently averaged 23 oestrus cycles with an average length of 17 days. Damara ewes showed greater mean peak plasma P4 levels (11.4±0.16ng/ml) than Swakara ewes (5.4±0.11ng/ml) (P<0.05). Oestrus cycles in Damara ewes showed relatively uniform plasma P4 peaks througho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…Studies have often reported that neonatal mortality rates differ between different breeds (Mukasa-Mugerwa et al 2000;Swarnkar et al 2019;Topal et al 2017). The Dorper is a synthetic breed, fashioned through the fusion of two exotic breeds, and the Damara has literally tracked down from North Africa to southern western Africa, over several hundreds of years, from its origins in Asia (Kandiwa et al 2019). According to a number of reports, the Damara has adapted to local disease and production conditions, breeds throughout the year, and has a good mothering ability (Almeida 2011;Kandiwa et al 2019;von Wielligh 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have often reported that neonatal mortality rates differ between different breeds (Mukasa-Mugerwa et al 2000;Swarnkar et al 2019;Topal et al 2017). The Dorper is a synthetic breed, fashioned through the fusion of two exotic breeds, and the Damara has literally tracked down from North Africa to southern western Africa, over several hundreds of years, from its origins in Asia (Kandiwa et al 2019). According to a number of reports, the Damara has adapted to local disease and production conditions, breeds throughout the year, and has a good mothering ability (Almeida 2011;Kandiwa et al 2019;von Wielligh 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Significantly more winter-born than summer-born Dorper and Swakara lambs weighed below 3 kg than in summer. It is surprising that the majority of Damara lambs were born in winter with weights greater than 3 kg especially when recent reports are pointing out that the breed now breeds equally well throughout the year in the Namibia climate (Kandiwa et al 2019). Earlier reports, however, have conflicting views on the effect of lambing/kidding season on birth weight with some reporting higher birth weights in winter-born lambs (Doaa et al 2009;Fasae et al 2012) and yet others reporting higher birth weights in summer-born lambs (Barzdina and Kairisa 2015;Hagan et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The country’s central highlands receive an annual rainfall of between 300 mm and 400 mm and have an altitude of up to 1900 m (Kandiwa et al 2017 ). The vegetation is predominantly shrub-veld and ambient temperatures range from 7 °C in winter to 33 °C in summer (Kandiwa et al 2019 ). The Khomas region has about 556 farming establishments, with approximately 44 000 primarily commercial beef cattle (Directorate of Veterinary Services 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…The country's central highlands receive an annual rainfall of between 300mm and 400mm and have an altitude of up to 1900 metres (Kandiwa et al, 2017). The vegetation is predominantly shrub-veld, and ambient temperatures range from 7 o C in winter and up to 33 o C in summer (Kandiwa et al, 2019). The Khomas region has approximately 560 livestock farming units, mainly commercial and some resettlement farms and communal settlements (Directorate of Veterinary Services, 2018).…”
Section: Study Areamentioning
confidence: 99%